Oracle GoldenGate 12c implementer's guide : leverage the power of real-time data access for designing, building, and tuning your GoldenGate Enterprise /: leverage the power of real-time data access for designing, building, and tuning your GoldenGate Enterprise. (2015) - Jeffries, John P
No abstract available